Direct Conversion of Food Waste into 3D Porous Carbon Traps for Selective Adsorption of Cationic Dyes. Issue 1 (19th October 2022) - Senthamizhan, Anitha; Balusamy, Brabu; Debellis, Doriana; Heredia‐Guerrero, Jose Alejandro; Mancini, Giorgio; Carzino, Riccardo; Ceseracciu, Luca; Athanassiou, Athanassia; Fragouli, Despina
Abstract: Conversion of waste biomass into valuable functional materials accomplishes the concept of circular economy in the development of sustainable waste management, and also recovery of such resources possibly reduces the requirement of feedstocks. In this scenario, the development of methodologies toward the direct conversion of the raw biomass into solid adsorbent materials without the use of any templates is highly desirable, but exceptionally challenging due to the complexity of the process. Here the direct synthesis of 3D porous carbon traps by a simple, cost‐effective, and template‐free process starting from a kitchen‐based recipe and fermented food waste is described. Precisely, a robust carbon trap is formed with a spongy structure and highly interconnected hierarchical pores after the pyrolysis of a rice‐based foam in the air. The developed materials float on water and interact efficiently with cationic dyes at static conditions. Importantly, such performance of the 3D carbon traps is not affected in the presence of anionic dyes, indicating the excellent selectivity towards the adsorption of cationic dyes. The adsorbent can be easily recovered and reused for up to 3 cycles without releasing any byproducts, thus, without causing hazardous risk of any secondary pollution to the environment. Abstract : Conversion of food waste into high valued materials plays vibrant role in the circular economy and in the sustainable development. The fabrication of solid porous 3D carbon traps prepared from food waste by pyrolysis of a rice‐based foam at relatively low temperature is reported and charge‐specific uptake of dyes specifically meant for surface contaminated water is demonstrated at static conditions.